Poisonous plants and related toxins (CABI, 2004)
This book contains 86 chapters based on papers presented at the 6th International Symposium on Poisonous Plants (ISOPP6), August 2001, Glasgow, UK. A range of topics are covered, from poisonous plant biochemistry to toxic effects in animals (particularly grazing farm animals) and humans. The contents include the evolution of antinutrients and toxins in plants, biomedical applications of plant toxins, isolation, identification and effects of plant and fungal toxins, and the effect of plant toxins on aversion to plants in animal diets. This book is targeted at researchers in botany, plant chemistry, animal and veterinary sciences and human toxicology.